Psychometric Properties of the Turkish PTSD-Short Scale in a Sample of Undergraduate Students. Issue 3 (1st September 2016) - Evren, Cuneyt; Dalbudak, Ercan; Aydemir, Omer; Koroglu, Ertugrul; Evren, Bilge; Ozen, Secil; Coskun, Kerem Senol
ABSTRACT: Objective : The National Stressful Events Survey for Posttraumatic Stress Disorder (PTSD)-Short Scale (NSESSS-PTSD) allows dimensional self-rating assessment of PTSD according to the DSM-5. The aim of the present study was to evaluate psychometric properties of this scale as Turkish PTSD-Short Scale (PTSD-SS) in a sample of undergraduate students in Turkey. Method : Participants included 415 university students, among which 351 (84.8%) reported trauma and thus were included in the analysis. Participants were evaluated with the PTSD-SS and the PTSD Checklist Civilian (PCL-C) version. Results : Turkish version of the PTSD-SS was found to be psychometrically sound PTSD screening measure with high convergent validity when compared with PCL-C (r=0.79) and having a Cronbach's a of 0.87. In addition, a single component accounted for 49.94% of total variance for PTSD-SS. The PTSD-SS had sensitivity and specificity scores of 0.91 and 0.77, respectively, when using the optimal cut-off score of 24. Additionally, the PTSD-SS showed good discriminant validity as it significantly differentiated students with high risk of PTSD from those with low risk of PTSD. Conclusion : These findings supported the Turkish PTSD-SS as reliable and valid PTSD screening instrument with a unidimensional scale construct.